(untitled) (Journal of Philosophy, Culture and Political Science, 2022)
Today, some directions of cultural processes in the Republic of Kazakhstan have deviated from their natural nature and become propagandists of Western culture, which are only imitators. This process weakens national taste and consciousness, and at the same time begins to gradually displace the nation from its traditional culture. Imitation makes its conscious expansion into the national culture, especially the consciousness of young people. From the point of view of taking advantage of this moment, some public organizations, using elements of mass culture, adapt it to the sources of a single commercial project. If we note the reasons for allowing such a negative attitude, we should note the decline in cultural tastes, the regression of the formation and differentiation of value systems in culture and art, the lack of control by management organizations over the penetration and spread of foreign cultural movements. In addition, it is necessary to take into account the influence of the cyberbullying process, which is formed on the basis of information flow. These processes ultimately lead to the decline of real art and the deviation of national culture. Key words: philosophy of culture, western and eastern dichotomy, cultural deviation, western civilization, eastern spirituality, national consciousness, era of cyberbullying.